2014
DOI: 10.1007/s11414-014-9425-8
|View full text |Cite|
|
Sign up to set email alerts
|

Reducing Recidivism and Symptoms in Emerging Adults with Serious Mental Health Conditions and Justice System Involvement

Abstract: The peak years of offending in the general population and among those with serious mental health conditions (SMHC) are during emerging adulthood. There currently are no evidence-based interventions for reducing offending behavior among 18–21 year olds, with or without SMHC. This open trial examined outcomes from an adaptation of Multisystemic Therapy (MST), an effective juvenile recidivism reduction intervention, modified for use with emerging adults with SMHC and recent justice system involvement. MST for eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 102 publications
1
25
0
Order By: Relevance
“…However, only 10% of clients in the program were using other drugs and/or alcohol in the last 30 days of treatment, and only five clients in the program had new arrests for drug related offenses during treatment. Although these data are limited to that collected by the community-based program, the clinical data from the first 80 pilot cases of MST-EA is promising and is consistent with outcomes in the small open trial (Davis et al, 2015). In addition, we are identifying enhancements that might further improve outcomes.…”
Section: Clinical Data On Pilot Casesmentioning
confidence: 54%
See 1 more Smart Citation
“…However, only 10% of clients in the program were using other drugs and/or alcohol in the last 30 days of treatment, and only five clients in the program had new arrests for drug related offenses during treatment. Although these data are limited to that collected by the community-based program, the clinical data from the first 80 pilot cases of MST-EA is promising and is consistent with outcomes in the small open trial (Davis et al, 2015). In addition, we are identifying enhancements that might further improve outcomes.…”
Section: Clinical Data On Pilot Casesmentioning
confidence: 54%
“…Currently there are no proven effective interventions to reduce recidivism in EAs, with or without SMI, but MST-EA has been piloted over the past 4 years to target this high-risk population. Promising results from a small open trial demonstrating efficacy of MST-EA were recently published (Davis, Sheidow, & McCart, 2015). Presented here is the first description of the MST-EA model, as well as clinical data on all pilot cases to date and a case example that demonstrate important characteristics of the model.…”
mentioning
confidence: 99%
“…Studies have shown an association between mental health treatment and reduced rates of arrest and recidivism [10][11][12][13][14][15][16][17][18]. However, many Americans with mental health conditions who are at a higher risk of arrest, due to low income for example, go untreated [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, vocational outcomes (when looking at school and/or work) were weak. Overall, there was only a gain from 70% being in school and/or working pre-treatment to 73% being in school and/or working post-treatment (Davis et al, 2015). An enhancement of MST-EA was proposed, and a pilot randomized controlled trial was undertaken to examine different MST-EA approaches to enhancing vocational outcomes through comparing two versions of MST-EA Coaches.…”
mentioning
confidence: 99%
“…The investigators already established the safety, feasibility, and preliminary efficacy of this MST adaptation in a successfully completed study (Davis et al, 2015). Therefore, the purpose of the current study was to develop and investigate age-appropriate vocational supports for MST-EA clients, thus filling a critical gap in vocational support interventions for this disadvantaged population.…”
mentioning
confidence: 99%